Does Board Diversity Affect Company Value? - Zakaria, Adam; Nindito, Marsellisa; Nasution, Hafifah; Khairunnisa, Hera; Siregar, M. Edo S. (University of Merdeka Malang, 2021)
Diversity in a board of directors has a strong relationship, so it provides higher-level management with a better monitoring system. This research aims to provide empirical proof about the influence of the diversity of the board of commissioners (BOC) and board of directors (BOD) on company value. Diversity is measured with age, educational background, and nationality. This quantitative research used data drawn from the annual reports of manufacturing companies listed on the Indonesian Stock Exchange (IDX). Panel- data regression was used to test whether the diversity of BOC and BOD significantly influenced company value. This research collected and analyzed data for 62 manufacturing companies for the 2015–2019 period, providing a total of 320 observations. Company size and leverage were applied as control variables, and the results show that age, educational background, and nationality of BOC and BOD have a significant influence on company value. Sensitivity analysis supports these results. This study benefits many parties such as BOD in monitoring the company’s operations, financial analysts, and investors in an investment decision. DOI : https://doi.org/10.26905/jkdp.v25i2.5516